Revista digital sobre la memoria social de la parroquia rural Chavezpamba - Dávila Álvarez, Estefanía Cristina (2015)
The investigation of the Social Memory´s Chavezpamba Rural Parish, involves historical, cultural and identity events that are important to capture in the digital magazine to strengthen the traditions of the people of the parish. The inquiry, includes theoretical aspects of communication, culture, identity and new technologies through conceptual postulates from some authors such as: Jelin, Hallbwachs, Kaplún, Habermas, Freire and Canclini, and others, that support and validate the existence of social and historical memory inside of a society. The concepts addressed help to create meanings in each of the topics covered in the product, because there is the relationship between theory and practice; so it is necessary, before intervening in Chavezpamba, to have prior knowledge to apply learning through interactive dialogue with the people reviving and discovering forgotten facts.